Literature Review : Pengaruh Penerapan Model Pembelajaran Collaborative Problem Solving Terhadap Kemampuan Berpikir Kritis Matematis Siswa - Nur Syafina, Nur Syafina; Aisyah Nur Syam, Aisyah Nur Syam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The application of the Collaborative Problem Solving (CPS) learning model in mathematics learning has shown great potential in improving students' mathematical critical thinking skills. This study aims to comprehensively review scientific articles discussing the application of CPS in mathematics learning and its impact on students' critical thinking skills in the 2019-2025 period. The method used is a systematic literature review by searching through Google Scholar, databases using the keywords